Passive Immunization with Anti-Pertussis Toxin Humanized Monoclonal Antibody Mitigates Clinical Signs of Pertussis Infection in Newborn Baboons. (4th October 2017) - Maynard, Jennifer; Nguyen, Annalee; Wolf, Roman; Papin, James; Connelly, Sheila; Kaleko, Michael
Abstract: Background: Pertussis is a significant mortality risk in the developing world, killing up to 200, 000 infants annually. Maternal vaccination as a strategy to protect newborns has shown some success, but is unlikely to capture all eligible mothers. Hu1B7 is a monoclonal antibody (mAb) that potently neutralizes pertussis toxin. Hu1B7, when administered as part of a binary mAb cocktail, demonstrated therapeutic efficacy in pertussis-infected weanling baboons. Here, the prophylactic potential of hu1B7 to protect infants during their first few months, when mortality risk is highest, was evaluated. Methods: Neonatal baboons of normal gestational age (180 days ± 10), normal birth weight (~1.0kg), and anti-Fha titer < 5 IU/ml (verifying no prior exposure to Bordetella species) were recruited into the study. At 2 days of age, treated baboons received hu1B7 (40mg/kg, IV), while control animals were untreated. Serum levels of hu1B7 were followed for 5 weeks, at which time the animals were infected with 10 8 cfu of B. pertussis strain D420. Animals were monitored for clinical signs of disease. Results: Six controls and seven treated animals were evaluated. All animals were heavily colonized with B. pertussis during the first week after infection. Controls developed significant leukocytosis, most coughed, and three required euthanasia. In contrast, white blood cell counts for all treated animals remained within the normal range, coughing was virtually absent, and all animals maintained normal activity. As expected for a humanized mAb in a nonhuman primate, hu1B7 had an elimination half-life of 11.8±3.4 days. Conclusion: Protection of newborn baboons from pertussis was achieved by mAb administration 5 weeks prior to pertussis infection. Hu1B7, when systemically present, mitigated the clinical signs of pertussis, including leukocytosis and coughing, but did not prevent bacterial colonization. Assuming a half-life in humans of 3 weeks, mAb administration at birth could potentially provide 4 months of prophylaxis and is a viable strategy to complement maternal vaccination. Moreover, strategies that extend the mAb half-life and lower the dose could further support developing world application. Disclosures: J. Maynard, Synthetic Biologics, Inc.: Collaborator, Research support; A. Nguyen, Synthetic Biologics, Inc.: Collaborator, Research support; R. Wolf, Synthetic Biologics, Inc.: Collaborator, Research support;; J. Papin, Synthetic Biologics, Inc.: Collaborator, Research support; S. Connelly, Synthetic Biologics, Inc.: Employee, Salary; M. Kaleko, Synthetic Biologics, Inc.: Employee and Shareholder, Salary and stock options